FGF2 modulates cardiac remodeling in an isoform‐ and sex‐specific manner. Issue 4 (17th September 2013) - Nusayr, Eyad; Sadideen, Doraid Tarek; Doetschman, Tom
Abstract Pathological cardiac hypertrophy and cardiac fibrosis are remodeling events that result in mechanical stiffness and pathophysiological changes in the myocardium. Both humans and animal models display a sexual dimorphism where females are more protected from pathological remodeling. Fibroblast growth factor 2 (FGF2) mediates cardiac hypertrophy, cardiac fibrosis, and protection against cardiac injury, and is made in high molecular weight and low molecular weight isoforms (Hi FGF2 and Lo FGF2, respectively). Although some light has been shed on isoform‐specific functions in cardiac pathophysiology, their roles in pathologic cardiac remodeling have yet to be determined. We tested the hypothesis that Lo FGF2 and Hi FGF2 modulate pathological cardiac remodeling in an isoform‐specific manner. Young adult male and female mice between 8 and 12 weeks of age of mixed background that were deficient in either Hi FGF2 or Lo FGF2 (Hi KO or Lo KO, respectively) were subjected to daily injections of isoproterenol (Iso) for 4 days after which their hearts were compared to wild‐type cohorts. Post‐Iso treatment, female Lo KO hearts do not exhibit significant differences in their hypertrophic and fibrotic response, whereas female Hi KO hearts present with a blunted hypertrophic response. In male animals, Lo KO hearts present with an exacerbated fibrotic response and increased α‐smooth muscle actin protein expression, whereas Hi KO hearts present with a blunted fibrotic response and increased atrial natriuretic factor protein expression Thus, in female hearts Hi FGF2 mediates cardiac hypertrophy, whereas in male hearts Lo FGF2 and Hi FGF2 display an antithetical role in cardiac fibrosis where Lo FGF2 is protective while Hi FGF2 is damaging. In conclusion, cardiac remodeling following catecholamine overactivation is modulated by FGF2 in isoform‐ and sex‐specific manners.